A novel breath pattern model and analysis to minimize patient discomfort in medical ventilators - M. Deepa; R. Vidhyapriya; A. S. Raagul (Scientific Reports)
Abstract Typical waveforms used for the simulation of pressure and volume-controlled ventilation in medical ventilators have been extensively studied in the literature. The majority of simulation studies reported employ the step pattern or ramp pattern to model the pressure and flow variations in pressure/volume-controlled ventilation. It was observed that the above waveforms tend to add to the discomfort level of patients due to the presence of jerks in derivatives of pressure/flow variations; the pressure/flow variation of air and oxygen mixture should be smooth so that the patient discomfort is kept at a minimal level. To overcome the above-mentioned drawback, a careful study of the flow/pressure simulation using a cycloidal pattern during the inhalation and exhalation phases of the breath cycle was proposed and investigated in this work. Based on transient analysis of the pressure variation simulation, it was observed that the air and oxygen mixture delivered to the patient was relatively jerk-free due to the finite values of first and second-order derivatives of pressure/flow curves. Mathematical models of the proposed simulation study of the cycloidal pattern of flow variation in both pressure/volume-controlled ventilation, are formulated and presented for use by ventilator designers. A comparative study of the simulation of step, ramp and cycloidal profiles applied to the breath cycle in a typical pressure-controlled ventilation is carried out and a marginal decrease in tidal volumes was observed in the case of cycloidal profiles for a given set of ventilator settings and the results are discussed. A typical natural breath pattern of a healthy adult was experimentally measured using a CITRIX breath analyser and the above mathematical model for the volume-controlled ventilation was found to closely describe the natural breathing process, using statistical parameters. Thus, the proposed cycloidal profile of pressure/flow variations in medical ventilators will be a better alternative, when compared to the step/ramp profiles investigated in this work; further, the proposed cycloidal profile matches closely with the natural breath pattern, based on typical experimental studies.